Determining Land Use/Land Cover (LULC) Changes Using Remote Sensing Method in L?leburgaz and LULC Change's Impacts on SDGs - Agdas, Merve Guroglu; Yenen, Zekiye (EUROPEAN CENTER SUSTAINABLE DEVELOPMENT, 2023)
Urbanization is among the human activities that affect the quality of urban life and sustainable urban development at a global scale. For monitoring human-induced changes in cities, studies on the changes in land use/land cover (LULC) based on a series of satellite images along with geographic information systems (GIS) are widely used. This study aims to evaluate the LULC changes in Luleburgaz between 2001 and 2021. For this purpose, the impacts of urban growth on natural areas and how these areas are handled in the context of sustainable development goals are examined, and the effects of urbanization on land use change are evaluated. The accuracy of the LULC maps was evaluated by means of the general accuracy index and the Kappa index. The overall accuracy rates of the land use maps for 2001, 2010, and 2021 were 96.32%, 93.66%, and 95.91%, respectively, while Kappa values were 0.95, 0.91, 0.94. These results indicate that, due to the effect of rapid urbanization and population growth over the last two decades, the built environment increased by 4.82% and the agricultural land has decreased by 4.88%. This result is a testament to the upward trend in the built environment at the expense of depleting a significant amount of agricultural land. The findings of the study provide useful data that can aid authorities in making conscious decisions to achieve sustainable urban planning and to improve environmental conditions.
Keywords: Urbanization; Land use; land cover change; Agricultural land; Sustainable development goals (SDGs); Remote sensing; URBAN SPRAWL; ACCURACY; DYNAMICS; CITIES; COEFFICIENT; AGREEMENT; Environmental Sciences & Ecology